Impact of alcohol consumption on outcomes and potential of immune biomarkers for postoperative complications in trauma patients - Hammour, Mohammad Majd; Anuk, Yelda; Breinbauer, Regina; Aspera-Werz, Romina H.; Xin, Yuxuan; Chen, Guanqiao; Histing, Tina; Ehnert, Sabrina; Nüssler, Andreas K.; Döbele, Stefan (Frontiers in Immunology, 2025)
IntroductionAlcohol consumption is a significant risk factor for adverse outcomes in trauma patients. Despite this, effective predictive biomarkers for postoperative complications remain elusive. This study aims to identify potential immune system biomarkers associated with postoperative complications in trauma patients with a history of chronic alcohol consumption.MethodsA prospective cohort study was conducted on trauma patients admitted to a level 1 Trauma Center. Chronic alcohol consumption and drinking habits were assessed using the Alcohol Use Disorders Identification Test (AUDIT-C) questionnaire. Specifically, 26% of patients reported no alcohol consumption, 44% reported moderate alcohol consumption, and 30% were identified as having risky alcohol consumption. Acute systemic alcohol levels at the time of injury were not measured or considered in this study, as the focus was on chronic consumption patterns. Routine blood screening data were analyzed.ResultsExcept for CRP, blood values were comparable between patients with risky alcohol consumption and controls. However, CRP’s ability to predict complications in patients with risky alcohol consumption remained limited (ROC-AUC = 0.6288). In order to identify other predictive markers, patients were matched based on relevant covariates in further analyses. Cytokine Array screening identified CD28, B7-1, Eotaxin-3, TIMP-1, and IL-13 as potential markers to predict complications. Verification with ELISA, however, showed that potential differences could only be detected in the control group. The discrepancies observed between cytokine array and ELISA results can be best explained by methodological differences, particularly since the serum samples were pooled for initial target screening. Additionally, variations in assay sensitivity, dynamic range, and calibration protocols contribute to these discrepancies.DiscussionThese findings suggest that chronic alcohol consumption alters cytokine responses, posing challenges for identifying reliable immune biomarkers for postoperative complications. Future studies should explore alternative approaches for biomarker validation and consider individualized assessment strategies for trauma patients with alcohol consumption history.